Pengaruh Kemampuan Berpikir Positif dan Kemandirian Belajar Terhadap Prestasi Belajar Fisika Siswa SMA Al Minhaj - Rida Risnanda (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The aim of this research is to find out: is there an indirect influence of positive thinking abilities on students' mathematics learning achievement through student learning independence. This research is correlational research using quantitative survey methods. The research subjects were 80 students at Al Minhaj High School. This survey research is quantitative research using structured/systematic questions, then all answers obtained by researchers are recorded, processed and analyzed as well as physic scores from student report cards. Data analysis uses path analysis. The independent variable in this research is physic learning achievement, while the dependent variable is the ability to think positively and learning independence. In the description of this research data, the results of the research from the data obtained include the highest score, lowest score, mean, mode, median, range/variance, and standard deviation/standard deviation. In processing the data obtained, the researcher carried out processing with the help of Microsoft Excel 2019 and SPSS 26 applications. Before the data was analyzed, a requirements test was first carried out, namely a normality test using the Liliefors test from Kosmogorov – Smirnov and a regression significance test using analysis of variance (ANAVA). From the results of normality testing for the independent variable positive thinking ability, a significance value of p = 0.922 > 0.05 was obtained; and the independent variable learning independence obtained a significance value of p = 0.652 > 0.05; while for the dependent variable physic learning achievement, the significance value was p = 0.783 > 0.05, so it can be concluded that the three samples have a normal distribution. Testing the linearity of the relationship between the positive thinking ability variable and the physic learning achievement variable obtained a significance value of p = 0.670 > 0.05; The relationship between independent learning and physic learning achievement obtained a significance value of p = 0.789 > 0.05; Meanwhile, the relationship between positive thinking ability and independence in learning physic has a significance value of p = 0.132 > 0.05, so it can be concluded that the regression model is linear, meaning that there is a linear relationship between the three variables. Hypothesis testing was carried out using path analysis, then calculating the significance of the correlation using the Student's t-test. The results of the path coefficient calculation show that t-count = 2.234 > ttable = 1.980 and the p-value (significant column) is 0.327, which means > 0.05, thus it can be concluded that there is a significant direct influence of positive thinking ability on physic learning achievement; tcount = 2.144 > ttable = 1.980 and the p-value (significant column) is 0.314, which means > 0.05, thus it can be concluded that there is a significant direct influence of learning independence on physic learning achievement; tcount = 11.832 > ttable = 1.980 and the p-value (significant column) is 0.796, which means > 0.05, thus it can be concluded that there is a significant direct influence of positive thinking ability on student learning independence.